Advances in creativity, innovation, entrepreneurship and communication of design proceedings of the AHFE 2021 virtual conferences on creativity, innovation and entrepreneurship, and human factors in communication of design, July 25-29, 2021, USA - Markopoulos, Evangelos; Goonetilleke, Ravindra S.; Ho, Amic G.; Luximon, Yan (Lecture Notes in Networks and Systems, 2021)
This book brings together experts from different areas to show how creativity drives design and innovation in different kind of businesses. It presents theories and best practices demonstrating how creativity generates technological invention, and how this, combined with entrepreneurship, leads to business innovation. It also discusses strategies to teach entrepreneurial competencies and support business developments, including aspects such as corporate social responsibility and sustainability. Moreover, the book discusses the role of human factors in understanding, communicating with and engaging users, reporting on innovative approaches for product design, development, and branding. It also discusses applications in education and well-being. Based on the AHFE 2021 Conferences on Creativity, Innovation and Entrepreneurship, and Human Factors in Communication of Design, held virtually on July 25-29 July, 2021, from USA, the book addresses a broad audience of business innovators, entrepreneurs, designers, and marketing and communication experts alike.